Fetal Hydronephrosis, A Case Report And Review of Literature (Journal of Paediatric Surgeons of Bangladesh, 2015)
With the increasing use of antenatal sonography, fetal hydronephrosis has been reported more frequently. Hydronephrosis is one of the most commonly identified prenatal anomalies, and the severity may vary from mild to severe, depending on the underlying cause. Many cases resolve spontaneously before birth, but for those that do not, the additional prenatal evaluation can identify cases sufficiently severe to require fetal intervention to preserve renal function. The benefits of these interventions must be balanced against the significant risks of the procedures and their sequelae in long-term efficacy. Evaluation before and after birth is warranted, and factors such as cause, severity, and whether the condition is uni- or bilateral are used to formulate decisions about additional assessment and potential intervention. Here we report a case of bilateral hydronephrosis which was detected during pregnancy. After delivery right side spontaneously resolves but there was worsening of left hydronephrosis in follow up and He undergoes a left pyeloplasty at 6 months of age and does well post operatively.J. Paediatr. Surg. Bangladesh 5(1): 36-38, 2014 (January)